Functional Connections of Cortical Areas : a New View from the Thalamus - Sherman, S. Murray (MIT Press, 2013)
This study shows new ways of thinking about how the brain relates to the world, to cognition, and to behaviour. Based on foundations previously established it considers the implications of these ground rules for thalamic inputs, thalamocortical connections, and cortical outputs. The book argues that functional and structural analyses of pathways connecting thalamus and cortex point beyond these to lower centres and through them to the body and the world.